Dampak Capital Intensity, Keberadaan Komisaris Independen dan Penggunaan Instrumen Derivatif terhadap Tingkat Agresivitas Pajak - Fitria Eka Ningsih; Hari Stiawan (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This research aims to examine and provide empirical evidence on the effect of capital intensity, the presence of independent commissioners, and the use of financial derivatives on tax aggressiveness. Using a quantitative approach, the study utilizes secondary data and applies panel data regression analysis with Eviews Version 12. The research population consists of 172 manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. From this population, a sample of 14 companies over a five-year period was selected. The findings reveal that capital intensity significantly influences tax aggressiveness, whereas independent commissioners and financial derivatives don’t have a significant impact